Character’s accentuations in the youth (Actual Problems of Psychology in Educational Institutions, 2019)
The article deals with the theoretical and methodologicalprinciples of the study of character’s accentuations. It describes the specific ofpsychological development in the youth. The article presets the results of theempirical research of the features of character’s accentuations in adolescence. Itis revealed which types of accentuations prevail in the representatives of thisage category and how they appear in the young people’s behavior. Сertaintypes of character’s accentuations were identified among 72% of respondents.Hyperthymic, cyclothymic, emotive types of accentuation expressed more often.Anxious, unbalanced and dysthymic types were not determined among thestudents. These types can significantly affect the development of deviantbehavior and social disadaptation of the individual.
Keywords: character’s accentuation, youth, social adaptation, deviant behavior, personality formation